Judisk idrottshistoria i Sverige – några anteckningar - Fischer, David (Nordisk judaistik/Scandinavian Jewish Studies, 1990)
The Jewish sports movement in Sweden was influenced from German Zionist youth associations. The first Jewish sports clubs in Sweden were founded in Stockholm and in Lund 1916. Until the late 30s the Jewish sports clubs encountered great skepticism from both Jewish congregations and well-established Swedish sport associations. This negative stance diminished when the events in Nazi-Germany become known. During the war, sports clubs were in a crucial position to support and reinforce Jewish identity and self-perception. Sport clubs also played a part in the integration of Jewish refugees. The post-war period was an expansive era in Swedish Jewish sports history.